(untitled) (American International Journal of Sciences and Engineering Research, 2023)
In recent years, nanofluids have been extensively utilized to improve heat transmission in various mediums. The use of nanofluids can enhance the thermal efficiency of thermosyphons. This study focuses on analyzing the thermal efficiency of automobile radiators by utilizing three different types of nanofluids. In this study, we conducted a thermal performance analysis of a car radiator by examining the effects of three different types of nanoparticles mixed with water: CuO-water, ZnO-water, and MgO-water nanofluids. The thermal performance of these three nanofluids was compared and analyzed. The experimental setup included a radiator with a hydraulic diameter of 0.0191 m and a total length of the radiator channel of 10.5354 m. The analyses are conducted at different volume fractions, ranging from 0.5% to 3%, and a constant inlet velocity of 0.24 m/s is maintained. The findings demonstrated a substantial enhancement in thermal efficiency when employing CuO-water nanofluid as a coolant for vehicle engine cooling in the radiator. Conversely, ZnO-water and MgO-water nanofluids exhibited very limited improvements in comparison to pure water. The thermal conductivity of CuO-water nanofluid is greater than that of pure water. The CuO-water nanofluid yields the most significant enhancements in terms of the mass flow rate and heat transfer coefficient, as revealed by this investigation. Hence, it is advisable to utilize CuO-water nanofluid in automobile radiators to achieve optimal heat transfer efficiency in comparison to the base fluid. JEL Classification Codes: O31, O32, Q40.